Management of a rare intra-articular fracture of the lateral femoral condyle: case report. - Compagnoni, Riccardo; Ricci, Martina; Pedrini, Francesca Alice; Ferrua, Paolo; Menon, Alessandra; Randelli, Pietro Simone (Acta Biomedica Atenei Parmensis, 2021)
Unicondylar fractures of the femur are uncommon injuries that can occur in the sagittal or, less frequently, in the coronal plane (Hoffa fractures).  Distal femoral fractures are usually described following the AO/OTA Classification system which includes extra-articular, partial articular and intra-articular injuries, further divided in three types based on the pattern and comminution.  Accurate reduction and stable fixation are needed especially in articular injuries in order to allow early mobilization and reduce complications such as knee stiffness, malunion or secondary osteoarthritis. The aim of this paper is to report a case of an unusual articular fracture of the lateral femoral condyle in a 39 years old man. This fracture reminds the pattern of a typical tibial plateau injury, not embedded in the most common descriptions of femoral traumas. Indeed, in most cases, high energy traumas in valgus of the knee result in a damage to the tibial plateau because of the condyles impact on the tibial articular surface, while in the present case the opposite occurred. The patient was successfully treated with an open reduction and fixation with two cannulated leg screws, reporting  good clinical outcome and excellent healing of the fragment evidenced with CT scan at 6 months follow-up.